2017
DOI: 10.3389/fpubh.2017.00193
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Public Health and Health Promotion Practice in the Medical Curriculum: A Self-Directed Team-Based Project Approach

Abstract: Preparing health professionals in health promotion (HP) and disease prevention is essential for improvement of population health, community HP, and better health care for individuals. The aim of this article is to describe an HP project in the form of a major self-directed project-based learning task integrated within the curriculum in the second year of the medical degree program at United Arab Emirates University. The project introduces students to public health and HP practice and develops students’ literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The inclusion of project-based learning will help students to better understand the importance of preventive behavior, improving their engagement with public health while building their research and analysis skills. 39 The longterm goal of service learning and advocacy training in medical curricula is to develop skilled and committed groups of students who can contribute to their communities whenever the need arises. This would inculcate students with a sense of responsibility, empathy, and interpersonal skills in the earliest years of their medical training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of project-based learning will help students to better understand the importance of preventive behavior, improving their engagement with public health while building their research and analysis skills. 39 The longterm goal of service learning and advocacy training in medical curricula is to develop skilled and committed groups of students who can contribute to their communities whenever the need arises. This would inculcate students with a sense of responsibility, empathy, and interpersonal skills in the earliest years of their medical training.…”
Section: Discussionmentioning
confidence: 99%
“…If adopted, they will provide students with the opportunity to understand the social determinants of health and available resources, as well as the importance of preventive behavior. The inclusion of project‐based learning will help students to better understand the importance of preventive behavior, improving their engagement with public health while building their research and analysis skills 39 . The long‐term goal of service learning and advocacy training in medical curricula is to develop skilled and committed groups of students who can contribute to their communities whenever the need arises.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the research articles revealed many advantages of SDL. Self-assessment, identifying skills, and confidence-building were the major advantages cited (1,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Various methods, such as problem-based learning, flipped classroom, and case-based learning, helped students work on themselves to gain knowledge, and analyze and interpret it with critical thinking, and also apply it leading to a definite diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Concepts from this standalone course are then connected in future courses and rotations throughout medical school (immunology, surgery, obstetrics/gynecology, pediatrics, internal medicine, geriatrics, etc.). Incorporate innovative team-based and project-based learning to improve knowledge and understanding of socio-ecological determinants, disease prevention, risk reduction, and health promotion ( 24 ); Post-coursework/standardized licensure testing : Increase the number of public health and nutrition questions, including knowledge key risk factors for leading causes of death on United States Medical Licensing Examinations; Research within training : Increase or reprioritize National Institutes of Health (NIH) research funding for student and residency research programs to place greater likelihood of awards for healthy equity research and social drivers of health. Establish mechanisms supporting public health practice and academic medicine partnerships; Clinical Practice : Develop innovative payer/reimbursement mechanisms such that risk-reduction practices are financially rewarded in primary care, acknowledging the initial steps of the Patient Protection and Affordable Care Act (ACA).…”
Section: Discussion and Recommendations For Reforming Medical Educatimentioning
confidence: 99%
“…Concepts from this standalone course are then connected in future courses and rotations throughout medical school (immunology, surgery, obstetrics/gynecology, pediatrics, internal medicine, geriatrics, etc.). Incorporate innovative team-based and project-based learning to improve knowledge and understanding of socio-ecological determinants, disease prevention, risk reduction, and health promotion ( 24 );…”
Section: Discussion and Recommendations For Reforming Medical Educatimentioning
confidence: 99%